THE EFFECT OF EARNING VOLATILITY, INCOME SMOOTHING AND EARNING PERSISTENCE ON EARNINGS QUALITY - Yoga Joko Sasongko; Siti Nur Azizah; sri Wahyuni; Ira Hapsari (Review of Applied Accounting Research (RAAR), 2021)
This study aims to examine the effect of earnings volatility, smoothing earnings and earningspersistence. The independent variables used in this study are earnings volatility, income smoothingand earnings persistence. The dependent variable used in this study is earnings quality. Themethod uses secondary data in annual reports or financial reports that have been published byIslamic banking companies listed on the Indonesia Stock Exchange for the period 2016-2019. Thesampling technique used in this study was purposive sampling, while the analysis used in this studywas multiple regression. The results of hypothesis testing showed that earnings volatility has apositive effect on earnings quality. Income smoothing has a positive effect on earnings quality.Earnings persistence does not affect earnings quality